Residence times of bank storage and return flows and the influence on river water chemistry in the upper Barwon River, Australia. (February 2019) - Howcroft, William; Cartwright, Ian; Cendón, Dioni I.
Abstract: Documenting the sources and residence times of water that contributes to streamflow is important for understanding processes in river catchments. The residence times of bank storage and return flow and its influence on river water chemistry in the upper Barwon River of southeast Australia were investigated using stable ( 18 O, 2 H, and 13 C) and radioactive ( 3 H and 36 Cl) isotopes, major ion geochemistry, river discharge data, and electrical conductivity (EC)-discharge hysteresis. Elevated 3 H activities following high winter flows indicate that bank storage and return flow contributes to river discharge for at least several months. However, EC-discharge hysteresis patterns suggest that individual storm events make additional contributions to bank storage and return flow throughout the year over periods of a few weeks. 3 H activities in the upper Barwon River are >1.75 TU throughout the year, suggesting that the contribution of older regional groundwater, which has 3 H activities <0.04 TU, is relatively minor in comparison to bank return flows. However, downstream trends in total dissolved solids (TDS) concentrations, δ 13 C values and R 36 Cl values demonstrate that regional groundwater inflows deliver solutes to the river. Estimates of regional groundwater inflows are mainly in the range 8–33% of total stream flow. The R 36 Cl values of river water in the upper Barwon catchment are between 37 and 46, which are significantly higher than those of modern rainfall (∼20). The high R 36 Cl values may reflect retardation of bomb-pulse 36 Cl due to plant uptake and recycling in the soil zone, which suggests Cl residence times of up to ∼60 years. The results of this study demonstrate that river water is comprised of both young and old water and that managing rivers and near-river environments should include careful consideration of both inputs. Highlights: Bank storage and return flow following high winter streamflow has a residence time of several months, if not longer. Bank storage and return flow following individual storm events has a residence time on the order of a few wees High chlorine-36 ratios in river water may be due to plant uptake and recycling of bomb-pulse 36-Cl in soils.